Understanding the Impact of Cultural Dynamics on Millennial Entrepreneurs’ Work Practices - Lichy, Jessica (Management international / International Management / Gestiòn Internacional, 2024)
This study explores how cultural context influences the work practices of millennial entrepreneurs in Russia, Latvia, Lithuania and Kazakhstan. Using theories of culture and planned behaviour, interviews were conducted to address the research question: “How does cultural context influence millennial entrepreneurs’ work practices in Russia, Latvia, Lithuania and Kazakhstan?” Findings reveal commonalities (e.g., communication style, trust-building, autonomy) and divergences (e.g., initiative, dialogue initiation, affiliations), indicating cultural values significantly affect Hofstede’s framework country scores. Two cliques hindering entrepreneurship were identified. The study highlights that collectivism does not extend to work practices and communication, questioning Hofstede’s framework relevance. The contribution lies in providing empirical data in an understudied context, serving as a benchmark for further research on cultural shifts in international management.